Reducing Abuse Liability of GABA(A)/Benzodiazepine Ligands via Selective Partial Agonist Efficacy at α(1) and α(2/3) Subtypes - Ator, Nancy A. (The American Society for Pharmacology and Experimental Therapeutics, 2010)
Abuse-liability-related effects of subtype-selective GABA(A) modulators were explored relative to the prototypic benzodiazepine lorazepam. 7-Cyclobutyl-6-(2-methyl-2H-1,2,4-triazol-3-ylmethoxy)-3-phenyl-1,2,4-triazolo[4,3-b]pyridazine (TPA123) has weak partial agonist efficacy at α(1)-, α(2)-, α(3)-, and α(5)-containing GABA(A) receptors, whereas 7-(1,1-dimethylethyl)-6-(2-ethyl-2H-1,2,4-triazol-3-ylmethoxy)-3-(2-fluorophenyl)-1,2,4-triazolo[4,3-b]pyridazine (TPA023) has weaker partial agonist efficacy at α(2) and α(3) and none at α(1) and α(5) subtypes. For both compounds, preclinical data suggested efficacy as nonsedating anxiolytics. Self-injection of TPA123 (0.0032–0.1 mg/kg) and TPA023 (0.0032–0.32 mg/kg) was compared with lorazepam (0.01–0.32 mg/kg) in baboons. TPA123 and lorazepam maintained self-injection higher than vehicle at two or more doses in each baboon; peak rate of self-injection of lorazepam was higher than TPA123. Self-injected lorazepam and TPA123 also increased rates of concurrently occurring food-maintained behavior. After the availability of self-administered TPA123 doses ended, an effect consistent with a mild benzodiazepine-like withdrawal syndrome occurred. In contrast with lorazepam and TPA123, TPA023 did not maintain self-administration. Positron emission tomography studies showed that TPA023 produced a dose-dependent inhibition in the binding of [(11)C]flumazenil to the benzodiazepine binding site in the baboon, which was essentially complete (i.e., 100% occupancy) at the highest TPA023 dose (0.32 mg/kg). In a physical dependence study, TPA023 (32 mg/kg/24 h) was delivered as a continuous intragastric drip. Neither flumazenil at 14 days nor stopping TPA023 after 30 to 31 days resulted in the marked withdrawal syndrome characteristic of benzodiazepines in baboons. In the context of other data, elimination of efficacy at the α(1) subtype of the GABA/benzodiazepine receptor is not sufficient to eliminate abuse liability but may do so when coupled with reduced α(2/3) subtype efficacy.